Improving the Competence of Junior High School Teachers in Designing Instructional Material and Assessment for the Implementation of the Kurikulum Merdeka - Fuja Novitra; Rio Anshari; Khairil Arif (Fakultas MIPA Universitas Negeri Padang, 2026)
The digital technology–driven pedagogical transformation has established new standards in modern learning practices, including increased demands for flexibility, innovation, and adaptive instructional approaches. In Indonesia, the Merdeka Curriculum represents a strategic response to these developments by emphasizing differentiated instruction and the integration of digital technologies to address diverse student learning needs. This Community Partnership Program (PKM) was designed to support science teachers affiliated with the Science Subject Teachers’ Forum (MGMP IPA) of Solok City in strengthening their pedagogical and digital competencies through structured training on the development of digital learning materials and assessments grounded in differentiated instruction. The program was implemented through several stages, including preparation, delivery of conceptual content, hands-on digital product development, and evaluation of participants’ competencies. The evaluation results indicate positive outcomes, including enhanced understanding of digital learning trends (87%), improved ability to implement differentiated instruction (82%), and increased competence in developing digital learning materials and assessments (83%). These findings demonstrate that technology-based training provides a substantive contribution to reinforcing teachers’ readiness to meet the demands of the Merdeka Curriculum. The practical implication underscores the need for sustained and scalable training initiatives to further support broader educational transformation.